Change in Seasonality Pattern of EU Farmgate Milk Price - Olipra, Jakub (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2019)
Since 2007 farmgate milk prices in EU have become much more volatile and their seasonal pattern has stopped being so explicit. The purpose of this research is to test the hypothesis that seasonality still plays an important role in shaping farmgate milk prices in EU while its amplitude decreases together with the growing integration of the EU milk market with the global market. The aforementioned issues are investigated using Census X-12 procedure of price decomposition and panel random effects model. The results indicate that after 2007 the role of seasonality in determining EU farmgate milk prices has significantly decreased which partially results from the higher integration of the EU milk market with the global market. Nevertheless, seasonality remains an important factor determining the farmgate milk prices in EU. It can be expected that with the further globalization of the milk market, the significance of seasonality in determining farmgate milk prices in EU will be diminishing.